Pengaruh Karakteristik dan Riwayat Penyakit Kronis terhadap Kejadian Depresi pada Lansia yang Tinggal di Roujin Home Asahi No Ie Jepang - Wahyu Nur Hidayat; Mariah Ulfah; Ema Wahyu Ningrum (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Depression is one of the most common mental health problems experienced by older adults and is influenced by various factors, including individual characteristics and chronic disease conditions. This study aims to determine the influence of age, gender, and chronic disease history on the incidence of depression among older adults residing at Roujin Home Asahi No Ie, Japan. The study used a quantitative method with a cross-sectional design. The population consisted of all elderly individuals living at Roujin Home Asahi No Ie, and the sampling technique used was total sampling. The Geriatric Depression Scale (GDS) was utilized as the instrument to measure depression levels. Data were analyzed using univariate and bivariate analyses with the Chi-Square test. The results showed a significant relationship between age and depression levels (p = 0.001), indicating that older age increases the risk of depression. Gender also demonstrated a significant association with depression (p = 0.015), showing differences in vulnerability between male and female elderly individuals. In addition, a significant relationship was found between chronic disease history and depression (p = 0.002), indicating that elderly individuals with chronic illnesses are more likely to experience depression. Based on these findings, it can be concluded that age, gender, and chronic disease history significantly influence depression among older adults. These results are expected to support the development of preventive strategies and geriatric nursing interventions to improve mental health and quality of life among elderly individuals in nursing home environments.